Non-contact anterior cruciate ligament injury epidemiology in team-ball sports: a systematic review with meta-analysis by sex, age, sport, participation level, and exposure type - Chia, L.; De Oliveira Silva, D.; Whalan, M.; McKay, M. J.; Sullivan, J.; Fuller, C. W.; Pappas, E. (Sports Medicine, 2022)
Background: Not all anterior cruciate ligament (ACL) injuries are preventable. While some ACL injuries are unavoidable such as those resulting from a tackle, others that occur in non-contact situations like twisting and turning in the absence of external contact might be more preventable. Because ACL injuries commonly occur in team ball-sports that involve jumping, landing and cutting manoeuvres, accurate information about the epidemiology of non-contact ACL injuries in these sports is needed to quantify their extent and burden to guide resource allocation for risk-reduction efforts. Objective: To synthesize the evidence on the incidence and proportion of non-contact to total ACL injuries by sex, age, sport, participation level and exposure type in team ball-sports. Methods: Six databases (MEDLINE, EMBASE, Web of Science, CINAHL, Scopus and SPORTDiscus) were searched from inception to July 2021. Cohort studies of team ball-sports reporting number of knee injuries as a function of exposure and injury mechanism were included. Results: Forty-five studies covering 13 team ball-sports were included. The overall proportion of non-contact to total ACL injuries was 55% (95% CI 48-62, I2 = 82%; females: 63%, 95% CI 53-71, I2 = 84%; males: 50%, 95% CI 42-58, I2 = 86%). The overall incidence of non-contact ACL injuries was 0.07 per 1000 player-hours (95% CI 0.05-0.10, I2 = 77%), and 0.05 per 1000 player-exposures (95% CI 0.03-0.07, I2 = 97%). Injury incidence was higher in female athletes (0.14 per 1000 player-hours, 95% CI 0.10-0.19, I2 = 40%) than male athletes (0.05 per 1000 player-hours, 95% CI 0.03-0.07, I2 = 48%), and this difference was significant. Injury incidence during competition was higher (0.48 per 1000 player-hours, 95% CI 0.32-0.72, I2 = 77%; 0.32 per 1000 player-exposures, 95% CI 0.15-0.70, I2 = 96%) than during training (0.04 per 1000 player-hours, 95% CI 0.02-0.07, I2 = 63%; 0.02 per 1000 player-exposures, 95% CI 0.01-0.05, I2 = 86%) and these differences were significant. Heterogeneity across studies was generally high. Conclusion: This study quantifies several key epidemiological findings for ACL injuries in team ball-sports. Non-contact ACL injuries represented over half of all ACL injuries sustained. The proportion of non-contact to total ACL injuries and injury incidence were higher in female than in male athletes. Injuries mostly occurred in competition settings.